Patterns of vestibular impairment in bilateral vestibulopathy and its relation to etiology - Van Stiphout, Lisa; Pleshkov, Maksim O.; Lucieer, Florence; Dobbels, Bieke; Mavrodiev, Vergil; Guinand, Nils; Perez Fornos, Angelica; Widdershoven, Josine; Strupp, Michael; Van Rompaey, Vincent; van de Berg, Raymond (Frontiers in neurology)
ObjectiveThis study aimed to investigate (1) the patterns of vestibular impairment in bilateral vestibulopathy (BVP) and subsequently, the implications regarding patient eligibility for vestibular implantation, and (2) whether this pattern and severity of vestibular impairment is etiology dependent. MethodsA total of one hundred and seventy-three subjects from three tertiary referral centers in Europe were diagnosed with BVP according to the Barany Society diagnostic criteria. The subjects underwent vestibular testing such as the caloric test, torsion swing test, video Head Impulse Test (vHIT) in horizontal and vertical planes, and cervical and/or ocular vestibular evoked myogenic potentials (c- and oVEMPs). The etiologies were split into idiopathic, genetic, ototoxicity, infectious, Meniere's Disease, (head)trauma, auto-immune, neurodegenerative, congenital, and mixed etiology. ResultsThe caloric test and horizontal vHIT more often indicated horizontal semicircular canal impairment than the torsion swing test. The vHIT results showed significantly higher gains for both anterior canals compared with the horizontal and posterior canals (p < 0.001). The rates of bilaterally absent oVEMP responses were higher compared to the bilaterally absent cVEMP responses (p = 0.010). A total of fifty-four percent of the patients diagnosed with BVP without missing data met all three Barany Society diagnostic test criteria, whereas 76% of the patients were eligible for implantation according to the vestibular implantation criteria. Regarding etiology, only horizontal vHIT results were significantly lower for trauma, neurodegenerative, and genetic disorders, whereas the horizontal vHIT results were significantly higher for Meniere's Disease, infectious and idiopathic BVP. The exploration with hierarchical cluster analysis showed no significant association between etiology and patterns of vestibular impairment. ConclusionThis study showed that caloric testing and vHIT seem to be more sensitive for measuring vestibular impairment, whereas the torsion swing test is more suited for measuring residual vestibular function. In addition, no striking patterns of vestibular impairment in relation to etiology were found. Nevertheless, it was demonstrated that although the implantation criteria are stricter compared with the Barany Society diagnostic criteria, still, 76% of patients with BVP were eligible for implantation based on the vestibular test criteria. It is advised to carefully examine every patient for their overall pattern of vestibular impairment in order to make well-informed and personalized therapeutic decisions.